One Solution for Many Linear Partial Differential Equations With Terms of Equal Orders - Miranda, Lohans de Oliveira; Miranda, Lossian Barbosa Bacelar (Journal of Nepal Mathematical Society, 2021)
We disclose a simple and straightforward method of solving single-order linear partial differential equations. The advantage of the method is that it is applicable to any orders and the big disadvantage is that it is restricted to a single order at a time. As it is very easy compared to classical methods, it has didactic value.